2016
DOI: 10.4137/cmped.s38503
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Apgar Score with Asphyxial Hepatic Injury and Mortality in Newborns: A Prospective Observational Study from India

Abstract: OBJECTIVEThe objective of this study is to determine the correlation of Apgar score with asphyxial hepatic injury and neonatal mortality in moderately and severely asphyxiated newborns.MATERIAL AND METHODSThis is a secondary analysis of our prospective observational case-controlled study. Sixteen neonates with severe birth asphyxia (five-minute Apgar ≤3) were compared with either 54 moderate asphyxia neonates (five-minute Apgar >3) or 30 normal neonates. Liver function tests were measured on postnatal days 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…However, a few surveys have looked at the effects of SPA on serum bilirubin with inconsistent results. While some reports have indicated that SPA is associated with a low risk of hyperbilirubinaemia, [2,3,[10][11][12] others have postulated that SPA is often accompanied with a rise in serum bilirubin [4,13,14]. Our findings are more correlated to the former.…”
Section: Discussionsupporting
confidence: 45%
“…However, a few surveys have looked at the effects of SPA on serum bilirubin with inconsistent results. While some reports have indicated that SPA is associated with a low risk of hyperbilirubinaemia, [2,3,[10][11][12] others have postulated that SPA is often accompanied with a rise in serum bilirubin [4,13,14]. Our findings are more correlated to the former.…”
Section: Discussionsupporting
confidence: 45%
“…A low 5-minute Apgar score alone was correlated to elevated LDH. 10 The negative predictive value of the 5-minute Apgar score is the more reliable indicator; wherein a score of 7 or greater, "it is unlikely" that peripartum hypoxia would cause neonatal encephalopathy. 11 The mean 5-minute Apgar score for our cohort was 8.7.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on perinatal asphyxia with or without HIE consistently show that the LDH in newborns with moderate and severe asphyxia peaks on day 3 after which it gradually decreases, normalizing within 10 days of life. 2,10,17 In mildly asphyxiated newborns, the elevated day 1 LDH decreased by day 3. 10,17 Thus, persistently raised and increasing LDH levels on day 3 in both our respiratory distress groups would be explained by perinatal asphyxia only if it was moderate or severe; however, we had no demonstrable perinatal asphyxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a study conducted by Seikku et al (2016), low APGAR score at the fifth and tenth minutes of birth reflected asphyxia which could predict neonatal mortality. Another study conducted by Sharma et al (2012) found that low APGAR score in neonates had a 2.23 times risk of having neonatal death compared to neonates with high APGAR score. The low APGAR score reflected the level of service availability and service standards that were not appropriate during delivery (Berglund et al, 2010).…”
Section: Introductionmentioning
confidence: 96%